Determinants of Patient‐Physician Discordance in Global Assessment in Psoriatic Arthritis: A Multicenter European Study. Issue 10 (6th September 2017) - Desthieux, Carole; Granger, Benjamin; Balanescu, Andra Rodica; Balint, Peter; Braun, Jürgen; Canete, Juan D.; Heiberg, Turid; Helliwell, Philip S.; Kalyoncu, Umut; Kvien, Tore K.; Kiltz, Uta; Niedermayer, Dora; et al.
Abstract : Objective: Patient‐physician discordance in global assessment of disease activity concerns one‐third of patients, but what does it reflect? We aimed to assess patient‐physician discordance in psoriatic arthritis (PsA) and patient‐reported domains of health (physical and psychological) associated with discordance. Methods: We analyzed the PsAID (Psoriatic Arthritis Impact of Disease), a cross‐sectional, multicenter European study of patients with PsA according to expert opinion. Patient global assessment (PGA) and physician global assessment (PhGA) were rated on a 0–10 numeric rating scale. Discordance was defined as the difference (PGA−PhGA) and as the absolute difference |PGA−PhGA| ≥3 points. Determinants of PGA−PhGA were assessed by a stepwise multivariate linear regression among 12 physical and psychological aspects of impact: pain, skin problems, fatigue, ability to work/leisure, functional incapacity, feeling of discomfort, sleep disturbance, anxiety/fear, coping, embarrassment/shame, social participation, and depressive affects. Results: In 460 patients (mean ± SD age 50.6 ± 12.9 years, 52.2% female, mean ± SD disease duration 9.5 ± 9.5 years, mean ± SD Disease Activity Index for Psoriatic Arthritis score 30.8 ± 32.4, and 40.4% undergoing treatment with biologic agents), the mean ± SD PGA was higher than the mean PhGA, with a mean absolute difference of 1.9 ± 1.8 points. Discordance defined by |PGA−PhGA| ≥3 of 10 concerned 134 patients (29.1%), and 115 patients (85.8% of the patients with discordance) had PGA>PhGA. Higher fatigue (β = 0.14), lower self‐perceived coping (β = 0.23), and impaired social participation (β = 0.16) were independently associated with a higher difference (PGA−PhGA). Conclusion: Discordance concerned 29.1% of these patient/physician dyads, mainly by PGA>PhGA. Factors associated with discordance were psychological rather than physical domains of health. Discordance was more frequent in patients in remission, indicating more work is needed on the patient perspective regarding disease activity.